2022
DOI: 10.1126/science.abn8897
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for potent antibody neutralization of SARS-CoV-2 variants including B.1.1.529

Abstract: The rapid spread of the SARS-CoV-2 B.1.1.529 (Omicron) variant and its resistance to neutralization by vaccinee and convalescent sera are driving a search for monoclonal antibodies with potent neutralization. To provide insight into effective neutralization, we determined cryo-EM structures and evaluated receptor-binding domain (RBD) antibodies for their ability to bind and neutralize B.1.1.529. Mutations altered 16% of the B.1.1.529 RBD surface, clustered on a RBD ridge overlapping the ACE2-binding surface an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
144
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 63 publications
16
144
0
1
Order By: Relevance
“…In vitro studies have shown that AZD7442 and its parental antibodies (CoV-2130 plus CoV-2196) retain some neutralizing activity against the BA.1 subvariant of the B.1.1.259 (omicron) variant, with neutralizing activity reduced by a factor of 12 to 30 in live-virus assays 30-32 and by a factor of 132 to 183 in pseudovirus 30 , 33 assays. The potency of AZD7442 (half-maximal inhibitory concentration geometric mean titer of 51 to 277 ng per milliliter 33 , 34 ) is higher than that of convalescent serum; therefore, AZD7442 is likely to be clinically active against the BA.1 subvariant. Emerging evidence suggests that the neutralizing activity of AZD7442 against the BA.2 subvariant is only minimally lower than that against the wild-type virus (lower by a factor of five in live-virus assays and by a factor of three in pseudovirus assays).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that AZD7442 and its parental antibodies (CoV-2130 plus CoV-2196) retain some neutralizing activity against the BA.1 subvariant of the B.1.1.259 (omicron) variant, with neutralizing activity reduced by a factor of 12 to 30 in live-virus assays 30-32 and by a factor of 132 to 183 in pseudovirus 30 , 33 assays. The potency of AZD7442 (half-maximal inhibitory concentration geometric mean titer of 51 to 277 ng per milliliter 33 , 34 ) is higher than that of convalescent serum; therefore, AZD7442 is likely to be clinically active against the BA.1 subvariant. Emerging evidence suggests that the neutralizing activity of AZD7442 against the BA.2 subvariant is only minimally lower than that against the wild-type virus (lower by a factor of five in live-virus assays and by a factor of three in pseudovirus assays).…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant, which carries 37 mutations in the spike protein and 15 amino acid substitutions in the receptor-binding domain, appears to preferentially infect and replicate in the upper respiratory tract. This is in comparison to Delta and other variants that favor the lower respiratory tract, and Omicron has a decreased ability to infect lung tissue [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…A19-46.1 could not bind probes with L452R/Q mutation, as seen with S2P probes (Figs 3D , 6D and 7D ). Residue 452 is located in the center of the A19-46.1 epitope ( S1C Fig ) and plays an important role in binding interactions [ 40 ]. On the other hand, the Class III RBD antibody A19-61.1 substantially reduced binding to the B.1.1.529 RBD probe, which has mutations at residues 446 and 493 on the periphery of A19-61.1 epitope ( S1C Fig ), but retained binding to most other RBD or RBD-SD1 variant probes (Figs 6D and 7D ).…”
Section: Resultsmentioning
confidence: 99%